"There's No Fresh Air There: Narratives of Smoke Exposure among Residents of Extended-Stay Hotels. Issue 2 (27th February 2015) - Lewinson, Terri; Bryant, Lawrence Oliver
Abstract : Hotel environments have been identified as places where hospitality workers and patrons are at an increased risk for smoke exposure and associated health hazards. However, little research has been conducted to understand experiences of long-term hotel residents. This article presents narrative accounts of tobacco smoke exposure from 37 residents at extended-stay hotels in a large metropolitan Atlanta county. Residents' narratives included an awareness of smoking as an unhealthy habit but a shared activity that facilitates social engagement at the hotel. Secondhand smoke narratives included descriptions of exposure from roommates and hotel neighbors. Thirdhand smoke narratives included reports of persistent pollution and smoke residue in the hotel environment. These results suggest a need for further research to understand the extent and impact of tobacco smoke exposure among this understudied population. The implications of this research support the efforts of social workers to engage in clean air advocacy and policy making for a vulnerable population.